Physical, physiological and biochemical changes during the development of sorghum seeds with different concentrations of tannin - Tanismare Tatiana de Almeida; João Almir Oliveira; Sttela Dellyzete Veiga Franco da Rosa; Adriano Alves da Silva; Andrea dos Santos Oliveira; Diego de Sousa Pereira (Acta Agronómica)
With the interest of verifying the relationship among tannin concentration and seed dormancy, it was intended, in this research, to evaluate the biochemical, physical and physiological alterations occurred during the development of sorghum seeds with different concentrations of tannin. Seeds of cultivars BR 305 and BR 310, collected in seven development stages (100, 103, 107, 113, 119, 121, 127 days after sowing) according to water content. The seeds collected in each stage were divided into two lots, one submitted to drying at 35C to the moisture of 12% and the other lot without drying. The quality of seeds was evaluated by germination and enzyme profile tests. In addition, the tannin concentration in the seed in each development stage was measured. Beneficial effects of drying on germination of higher water seeds are found. In the seeds evaluated without drying, the percentage of dormancy is greater when compared to that of seeds submitted to artificial drying. For cultivar BR 305, drying favored tannin concentration in seeds collected in different development stages. The same occurred for cultivar BR 310 in seeds collected at 100, 103 and 119 days after sowing. For the enzyme profiles, increased activities of the enzyme alcohol dehydrogenase, malato dehydrogenase, catalase, a-amilase and catalase and esterase were observed in the seeds of the low tannin cultivar BR 310 and after drying.